Maybe soldiers have rights after all! - Jaeger, Nicole E. (Journal of Criminal Law & Criminology)
Part of a special section on Supreme Court review. In Loving v. United States, the Supreme Court assumed that the constitutional requirements of the Eight Amendment, as outlined in Furman v. Georgia, are applicable to the military. Given the Court's historical reluctance to interfere with the methods of military procedure, this assumption is significant. In making this assumption, the Court was aware of the historical necessities and events that have fashioned the modern military. Indeed, it was the focus on and understanding of English Constitutional history and the realities of the military today that allowed the Court to deviate from its typically deferential approach to military issues and undertake a more contemporary balancing of service-members' constitutional rights with military necessity. In light of the realities of the modern military establishment and the expansive reach of court-martial jurisdiction, the Court's assumption was correct.